Peran Keterampilan Dasar Mengajar dalam Meningkatkan Prestasi Siswa di SD - Sastri Dalila Siregar; Eka Yusnaldi; Nur Hafni Bahri Siambaton; Nurintan Maghfirah; Putri Aulia Sitorus; Ratika Balqis NST; Salsabila Putri Wibowo (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to analyze the role of basic teaching skills in improving student achievement. Basic teaching skills include the teacher’s ability to plan learning, manage the class, deliver material, and provide constructive evaluation and feedback. The research method used is a qualitative research method. The research results show that teachers who have good basic teaching skills are able to create a conducive learning environment, motivate students, and increase understanding of subject matter. Apart from that, these skills also contribute to improving students’ academic scores. The conclusion of this research confirms that the development of basic teaching skills is a key factor in efforts to improve student achievement. Therefore, training and professional development programs for teachers must be more focused on improving basic teaching skills to achieve optimal educational results.